Comparative genomics of the pathogenic ciliate Ichthyophthirius multifiliis, its free-living relatives and a host species provide insights into adoption of a parasitic lifestyle and prospects for disease control - Coyne, Robert S.; Hannick, Linda; Shanmugam, Dhanasekaran; Hostetler, Jessica B.; Brami, Daniel; Joardar, Vinita S.; Johnson, Justin; Radune, Diana; Singh, Irtisha; Badger, Jonathan H.; Kumar, Ujjwal; Saier, Milton; et al. (Genome Biology, 2011)
Background: Ichthyophthirius multifiliis, commonly known as Ich, is a highly pathogenic ciliate responsible for 'white spot', a disease causing significant economic losses to the global aquaculture industry. Options for disease control are extremely limited, and Ich's obligate parasitic lifestyle makes experimental studies challenging. Unlike most well-studied protozoan parasites, Ich belongs to a phylum composed primarily of free-living members. Indeed, it is closely related to the model organism Tetrahymena thermophila. Genomic studies represent a promising strategy to reduce the impact of this disease and to understand the evolutionary transition to parasitism. Results: We report the sequencing, assembly and annotation of the Ich macronuclear genome. Compared with its free-living relative T. thermophila, the Ich genome is reduced approximately two-fold in length and gene density and three-fold in gene content. We analyzed in detail several gene classes with diverse functions in behavior, cellular function and host immunogenicity, including protein kinases, membrane transporters, proteases, surface antigens and cytoskeletal components and regulators. We also mapped by orthology Ich's metabolic pathways in comparison with other ciliates and a potential host organism, the zebrafish Danio rerio. Conclusions: Knowledge of the complete protein-coding and metabolic potential of Ich opens avenues for rational testing of therapeutic drugs that target functions essential to this parasite but not to its fish hosts. Also, a catalog of surface protein-encoding genes will facilitate development of more effective vaccines. The potential to use T. thermophila as a surrogate model offers promise toward controlling 'white spot' disease and understanding the adaptation to a parasitic lifestyle.

Comparative genomics of the apicomplexan parasites toxoplasma gondii and neospora caninum: coccidia differing in host range and transmission strategy - Reid, Adam James; Vermont, Sarah J.; Cotton, James A.; Harris, David; Hill-Cawthorne, Grant A.; Koenen-Waisman, Stephanie; Latham, Sophia M.; Mourier, Tobias; Norton, Rebecca; Quail, Michael A.; Sanders, Mandy; Shanmugam, Dhanasekaran; et al. (Plos Pathogens, 2012)
Toxoplasma gondii is a zoonotic protozoan parasite which infects nearly one third of the human population and is found in an extraordinary range of vertebrate hosts. Its epidemiology depends heavily on horizontal transmission, especially between rodents and its definitive host, the cat. Neospora caninum is a recently discovered close relative of Toxoplasma, whose definitive host is the dog. Both species are tissue-dwelling Coccidia and members of the phylum Apicomplexa; they share many common features, but Neospora neither infects humans nor shares the same wide host range as Toxoplasma, rather it shows a striking preference for highly efficient vertical transmission in cattle. These species therefore provide a remarkable opportunity to investigate mechanisms of host restriction, transmission strategies, virulence and zoonotic potential. We sequenced the genome of N. caninum and transcriptomes of the invasive stage of both species, undertaking an extensive comparative genomics and transcriptomics analysis. We estimate that these organisms diverged from their common ancestor around 28 million years ago and find that both genomes and gene expression are remarkably conserved. However, in N. caninum we identified an unexpected expansion of surface antigen gene families and the divergence of secreted virulence factors, including rhoptry kinases. Specifically we show that the rhoptry kinase ROP18 is pseudogenised in N. caninum and that, as a possible consequence, Neospora is unable to phosphorylate host immunity-related GTPases, as Toxoplasma does. This defense strategy is thought to be key to virulence in Toxoplasma. We conclude that the ecological niches occupied by these species are influenced by a relatively small number of gene products which operate at the host-parasite interface and that the dominance of vertical transmission in N. caninum may be associated with the evolution of reduced virulence in this species.

Chromerid genomes reveal the evolutionary path from photosynthetic algae to obligate intracellular parasites - Woo, Yong H.; Ansari, Hifzur; Otto, Thomas D.; Klinger, Christen M.; Kolisko, Martin; Michalek, Jan; Saxena, Alka; Shanmugam, Dhanasekaran; Tayyrov, Annageldi; Veluchamy, Alaguraj; Ali, Shahjahan; Bernal, Axel; et al. (Elife, 2015)
The eukaryotic phylum Apicomplexa encompasses thousands of obligate intracellular parasites of humans and animals with immense socio-economic and health impacts. We sequenced nuclear genomes of Chromera velia and Vitrella brassicaformis, free-living non-parasitic photosynthetic algae closely related to apicomplexans. Proteins from key metabolic pathways and from the endomembrane trafficking systems associated with a free-living lifestyle have been progressively and non-randomly lost during adaptation to parasitism. The free-living ancestor contained a broad repertoire of genes many of which were repurposed for parasitic processes, such as extracellular proteins, components of a motility apparatus, and DNA-and RNA-binding protein families. Based on transcriptome analyses across 36 environmental conditions, Chromera orthologs of apicomplexan invasion-related motility genes were co-regulated with genes encoding the flagellar apparatus, supporting the functional contribution of flagella to the evolution of invasion machinery. This study provides insights into how obligate parasites with diverse life strategies arose from a once free-living phototrophic marine alga.

CSGID solves structures and identifies phenotypes for five enzymes in toxoplasma gondii - Lykins, Joseph D.; Filippova, Ekaterina V; Halavaty, Andrei S.; Minasov, George; Zhou, Ying; Dubrovska, Ievgeniia; Flores, Kristin J.; Shuvalova, Ludmilla A.; Ruan, Jiapeng; El Bissati, Kamal; Dovgin, Sarah; Roberts, Craig W.; et al. (Frontiers in Cellular and Infection Microbiology, 2018)
Toxoplasma gondii, an Apicomplexan parasite, causes significant morbidity and mortality, including severe disease in immunocompromised hosts and devastating congenital disease, with no effective treatment for the bradyzoite stage. To address this, we used the Tropical Disease Research database, crystallography, molecular modeling, and antisense to identify and characterize a range of potential therapeutic targets for toxoplasmosis. Phosphoglycerate mutase II (PGMII), nucleoside diphosphate kinase (NDK), ribulose phosphate 3-epimerase (RPE), ribose-5-phosphate isomerase (RPI), and ornithine aminotransferase (OAT) were structurally characterized. Crystallography revealed insights into the overall structure, protein oligomeric states and molecular details of active sites important for ligand recognition. Literature and molecular modeling suggested potential inhibitors and druggability. The targets were further studied with vivoPMO to interrupt enzyme synthesis, identifying the targets as potentially important to parasitic replication and, therefore, of therapeutic interest. Targeted vivoPMO resulted in statistically significant perturbation of parasite replication without concomitant host cell toxicity, consistent with a previous CRISPR/Cas9 screen showing PGM, RPE, and RPI contribute to parasite fitness. PGM, RPE, and RPI have the greatest promise for affecting replication in tachyzoites. These targets are shared between other medically important parasites and may have wider therapeutic potential.

Chronic systemic exposure to IL6 leads to deregulation of glycolysis and fat accumulation in the zebrafish liver - Singh, Manoj K.; Jayarajan, Rijith; Varshney, Swati; Upadrasta, Sindhuri; Singh, Archana; Yadav, Rajni; Scaria, Vinod; Sengupta, Shantanu; Shanmugam, Dhanasekaran; Shalimar; Sivasubbu, Sridhar; Gandotra, Sheetal; et al. (Biochimica ET Biophysica Acta-Molecular and Cell Biology of Lipids, 2021)
Inflammation is a constant in Non-Alcoholic Fatty Liver Disease (NAFLD), although their relationship is unclear. In a transgenic zebrafish system with chronic systemic overexpression of human IL6 (IL6-OE) we show that inflammation can cause intra-hepatic accumulation of triglycerides. Transcriptomics and proteomics analysis of the IL6-OE liver revealed a deregulation of glycolysis/gluconeogenesis pathway, especially a striking down regulation of the glycolytic enzyme aldolase b. Metabolomics analysis by mass spectrometry showed accumulation of hexose monophosphates and their derivatives, which can act as precursors for triglyceride synthesis. Our results suggest that IL6-driven repression of glycolysis/gluconeogenesis, specifically aldolase b, may be a novel mechanism for fatty liver. This mechanism may be relevant for NAFLD in lean individuals, an emerging class of NAFLD prevalent more in Asian Indian populations.
Keywords: Aldolase b; DHAP; Inflammation; Interleukin 6; Lean NAFLD; Non-alcoholic fatty liver

Conserved RNA binding activity of phosphatidyl inositol 5-phosphate 4-kinase (PIP4K2A) - Behari, Jatin; Borkar, Pranita; Vindu, Arya; Dandewad, Vishal; Upadrasta, Sindhuri; Shanmugam, Dhanasekaran; Seshadri, Vasudevan (Frontiers in Molecular Biosciences, 2021)
Plasmodium falciparum is a causative agent for malaria and has a complex life cycle in human and mosquito hosts. During its life cycle, the malarial parasite Plasmodium goes through different asexual and sexual stages, in humans and mosquitoes. Expression of stage-specific proteins is important for successful completion of its life cycle and requires tight gene regulation. In the case of Plasmodium, due to relative paucity of the transcription factors, it is postulated that posttranscriptional regulation plays an important role in stage-specific gene expression. Translation repression of specific set of mRNA has been reported in gametocyte stages of the parasite. A conserved element present in the 3 ` UTR of some of these transcripts was identified. Phosphatidylinositol 5-phosphate 4-kinase (PIP4K2A) was identified as the protein that associates with these RNA. We now show that the RNA binding activity of PIP4K2A is independent of its kinase activity. We also observe that PIP4K2A is imported into the parasite from the host on Plasmodium berghei and Toxoplasma gondii. The RNA binding activity of PIP4K2A seems to be conserved across species from Drosophila and C. elegans to humans, suggesting that the RNA binding activity of PIP4K may be important, and there may be host transcripts that may be regulated by PIP4K2A. These results identify a novel RNA binding role for PIP4K2A that may not only play a role in Plasmodium propagation but may also function in regulating gene expression in multicellular organisms.
Keywords: malaria; posttranscriptional gene regulation; RNA-protein interaction; translation regulation

Case report: a fatal case of babesiosis in a splenectomized male patient from Western India - Godbole, Ravi; Gaur, Avantika; Nayar, Priyanka; Kiruthiga, Kala; D'Costa, Pradeep; Manchanda, Rumma; Khilari, Ajinkya; Shanmugam, Dhanasekaran; Muglikar, Kalpana D.; Kundu, Krishnendu (American Journal of Tropical Medicine and Hygiene, 2022)
Human babesiosis is a rare disease, caused by Babesia species and commonly transmitted by tick bite. Although human babesiosis is known to be asymptomatic in immunocompetent hosts, clinical cases of severe babesiosis have been reported from splenectomized or immunocompromised individuals. To our knowledge, only one case of human babesiosis in India has been previously reported. Here, we report a case of severe babesiosis with high parasitemia (similar to 70%) in a 30-year-old asplenic farmer. The patient presented with fever, yellowish discoloration of skin, oliguria, and anemia; he eventually developed multiorgan failure syndrome and died. Peripheral blood films were prepared and used to confirm the presence of piroplasms by microscopy. Total DNA isolated from blood was used for 18S ribosomal RNA gene fragment amplification by polymerase chain reaction, which was subjected to Sanger sequencing. Although 18S sequence indicated that the Babesia species infecting the patient was similar to that of other Babesia species originating from wild mammals, species identification could not be done. Phylogenetic analysis revealed that the patientderived pathogen is distinct because it forms a separate clade in the cladogram.